Teacher Evaluation and Challenges in the School Literacy Movement: Implications for Improving Literacy Culture in Elementary Schools - Novi Putriani Sukamto; Tri Murwaningsih; Chumdari (Universitas Pendidikan Ganesha, 2025)
The literacy gap between urban areas and areas with limited resources emphasizes the urgency of evaluating the Gerakan Literasi Sekolah (GLS) in the context of basic education. Literacy, as an essential 21st-century skill, plays a strategic role in developing students' critical, creative, and adaptive thinking skills. This study aims to describe the effectiveness of GLS implementation in several elementary schools using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative approach was used with in-depth interviews, participant observation, and documentation studies involving teachers, principals, parents, and community leaders. Data were analyzed through stages of data reduction, categorization, thematic interpretation, and source triangulation to ensure the validity of the findings. The results indicate adequate policy support, teacher creativity in utilizing local resources, and increased student participation and interest in reading. However, limited literacy facilities, variety of reading materials, access to technology, and educators' digital competencies are major challenges in the sustainability of the program. This study emphasizes the importance of integrated interventions through strengthening literacy infrastructure, increasing technology-based teacher capacity, diversifying reading materials, and active community involvement. The practical implications lead to the development of an adaptive GLS model that can be replicated across primary school contexts to narrow the national literacy gap.